The Darien Region between Colombia and Panama: Gap or Seal? - Girot Pignot, Pascal Oliver (2002)
The Darien Gap stands, at the dawn of the XXIst Century, as a remainder of the linkages between local and global fenomena. At the crossroads of the Americas, bridge and canal, the Darien Gap remains un forded. A mere 80 miles separate the road networks of Nouth and South America, making the Darien the missing link in the Panamerican integration. It harbours of one of the most culturally and biologically diverse ecosystem of the neotropical region. It symbolizes in many ways the clash between constructs and realities, between the endless series of canal projects and interamerican road linkages and the extraordinary natural and cultural heritage of the Darien. It is also the scenario for the redefinition of the geopolitical makeup of northern South America. To which degree the humanitarian and military crisis unfolding in Colombia is going to bear on the immediate future of the Darien Gap is unclear. A cursory view of the players and issues at hand provides us with insight in the potential scenarios for environmental and human security in the region.